LEADERSHIP STYLE AND CHALLENGES OF DEVELOPMENT IN EAST AFRICAN REGION A Case study of South Sudan - Dr. Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
South Sudan faces a number of challenges in the years after independent. This challenges include internal conflict, communal violence, and other scandals. Relations between Juba, in South Sudan, and Khartoum are poor, and there are a number of unresolved issues between them. The crisis in the disputed area of Abyei remains a contentious issue, despite a temporary agreement reached in mid-June 2011. During the war, the SPLM maintained strong ties with many African countries and received political, financial, and military assistance from some governments. In the coming years, Congress is likely to remain active on issues related to South Sudan. U.S. assistance to South Sudan will be an important issue for Congress in light of the fact that South Sudan is one of the major recipients of U.S. assistance. The Obama Administration has requested 518 million for FY2012. The United States has maintained sanctions imposed on Sudan but removed them from South Sudan and other marginalized areas. However, there are current sanctions on Sudan that will have an impact on South Sudan even after independence. Congress is likely to deal with this issue in the coming months. The finding results revealed that leadership development is being influence by capacity a country ensure on its policies in regards to development strategies because leadership development depend on capacity of the country to frame up useful policies and develop strategies of achieving its goals. The majority according to the finding results shows that the level of literacy in the country influence leadership development in the country because the informed citizens who know their rights and functions of the government cannot be influence to support senseless conflicts. As majority of South Sudanese are illiterate, the country has been at war shortly after its independent from Sudan due to power greediness which cause political instability, socio-economic crisis, insecurity and total collapse of the governance system in the country. And that is why majority of the respondents traced out the prevailing conflict in the country a core challenge interrupting the political development. According to finding results, the interference of foreign powers into domestic affairs of the country is hindering the success of political development in so many aspects and has created rooms to government officials to misused public funds without accountability to unrest situation emerged by political instability and lack leadership skills to curb situations.